Implementation of a 900 V Switching Circuit for High Breakdown Voltage β-Ga2O3 Schottky Diodes. (1st January 2019) - Chen, Yen-Ting; Yang, Jiancheng; Ren, Fan; Chang, Chin-Wei; Lin, Jenshan; Pearton, S. J.; Tadjer, Marko J.; Kuramata, Akito; Liao, Yu-Te
Abstract : This paper presents a switching circuit for high breakdown-voltage Ga2 O3 vertical Schottky rectifiers. Field-plated edge-terminated (FPET) vertical Schottky diodes were fabricated on a 20-μm thick Si-doped n-type Ga2 O3 drift layer which was grown on the 650-μm thick β-Ga2 O3 substrate via halide vapor phase epitaxy (HVPE). The measured reverse recovery time of the proposed Ga2 O3 Schottky diode was 81 ns when switched to a reverse bias voltage of −900 V. The implementation of a switching circuit with the novel Ga2 O3 diode is the first demonstrated at such a high switching voltage. This paper also provides insights for the practical implementation of the Ga2 O3 vertical Schottky rectifiers from device fabrication to circuit design.